Critique de l’« orientation sexuelle » et de l’« identité de genre » dans le discours des droits humains : la politique queer mondiale au-delà des principes de Yogyakarta - Matthew Waites (Genre, Sexualité et Société)
This article presents a critique of the concepts "sexual orientation" and "gender identity", which are being employed to contest global human rights discourses by prevailing international lesbian, gay, bisexual and transgender (LGBT) and human rights activist networks – notably in the Declaration of Montreal (2006) and, especially, the Yogyakarta Principles (2007). Theoretical analysis, informed by social theory and queer theory, is presented of these key concepts shaping human rights debates, particularly in relation to the United Nations. Relationships between the discourses used by international governmental and non-governmental organizations (NGOs), academics and activists are analysed to discern the conceptions of subjectivity and identity operating. With reference to Judith Butler’s "heterosexual matrix", it is proposed that the entry of "sexual orientation" and "gender identity" into human rights discourse can be interpreted as installing a distinctive gender and sexuality matrix, but also that definitions of "sexual orientation" and "gender identity" in the Yogyakarta Principles facilitate contestation of these concepts. It is argued that LGBT, queer and allied NGOs and activists should systematically contest these concepts’ dominant meanings.